Small grain and semi-dwarf 3, a WRKY transcription factor, negatively regulates plant height and grain size by stabilizing SLR1 expression in rice - Jie Lan; Qibing Lin; Chunlei Zhou; Yakun Ren; Xi Liu; Rong Miao; Ruonan Jing; Changling Mou; Thanhliem Nguyen; Xingjie Zhu; Qian Wang; Xin Zhang; et al. (Plant Molecular Biology, 2020)

One new sterpurane sesquiterpene from cultures of the basidiomycete Pholiota nameko - Wan-Rong Niu; Cong-Liang Guo; Deng-Ji Lou; Rui-Ting Li; Qiao Xiang; Yu-Lin Zou; Xiu-Ming Cui; Xiao-Yan Yang (Natural Product Research, 2020)

Agrobacterium-mediated genetic transformation of Chinese chestnut (Castanea mollissima Blume) - Zhi-lin Sun; Xiao Li; Wan Zhou; Jun-di Yan; Yue-rong Gao; Xiao-wei Li; Jia-chen Sun; Ke-feng Fang; Qing Zhang; Yu Xing; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)
Chinese chestnut ( Castanea mollissima ) is an important germplasm resource for the breeding of Castanea species worldwide with vital ecological and economic value. Biotechnology overcomes the limitations of traditional breeding and accelerates germplasm improvement. However, a genetic transformation system for Chinese chestnut has not yet been established. In this study, a stable and efficient Agrobacterium -mediated genetic transformation method for Chinese chestnut is described. Embryogenic calli of C. mollissima cv. ‘Yanshanhongli’ were used as the target material. The sensitivity of embryogenic calli to kanamycin was determined, whereby the proliferation of non-transformed calli was completely inhibited at 180 mg/L. Antibiotic inhibition results for Chinese chestnut embryogenic calli showed that 50 mg/L cefotaxime and 500 μM timentin completely inhibited the growth of Agrobacterium tumefaciens but did not affect the normal growth of Chinese chestnut embryogenic calli. When embryogenic calli were co-cultured for 2 days with Agrobacterium tumefaciens strain AGL1 harboring the PBI121-EGFP plasmid, an embryogenic callus transformation efficiency of 4.55% was obtained, and two transgenic chimera were acquired. This Agrobacterium -mediated transformation system for Chinese chestnut provides a fundamental platform for genetic improvement of core germplasm and for further verification of gene function.